Deposition of methamphetamine residues produced by simulated smoking. (September 2022) - Russell, M.; Nicolle, Salomé; Mayo, Erina; Chappell, Andrew
Abstract: In New Zealand, many concerns have been raised over the presence of methamphetamine contamination in households, especially when its provenance is unknown. Previous research found that contamination levels on household surfaces were higher after the premises had been used as a clandestine laboratory. It is believed that the levels of contamination produced from smoking methamphetamine are much less than those produced through manufacture. This study's aim was to determine the amount of methamphetamine contamination produced, after simulated smoking, on a range of common, smooth surface types. Accumulation over time was also investigated. The experiment, comprising four simulated smoking events (referred to as 'smokes') of 0.2 g followed by a fifth simulated smoking event of 1.2 g (a cumulative total of 2 g) of methamphetamine hydrochloride, was carried out in a shipping container. Subsequent swabs were taken from squares of 100 cm 2, following the NIOSH 9111 method. Results were quantified using LC-MS/MS. The methamphetamine concentrations measured gave a range from an overall mean of 0.91 µg/100 cm 2 after the first smoke and 15.9 µg/100 cm 2 after the final smoke. A rate of accumulation for each surface type was established, as well as an order of surfaces showing the most to least observed contamination. A significant reduction in the level of contamination was observed over a short period of time, although a clear rate was not established. Finally, a relationship between the recovered amounts of methamphetamine and amphetamine produced through the pyrolysis (smoking) process was also determined. Highlights: Simulated smoking helps determine extent of methamphetamine surface contamination. Accumulation of methamphetamine contamination on various surfaces is assessed. Excessive levels of contamination can be used as evidence in forensic casework.